Cetuximab-induced cutaneous toxicity - Tomková, H; Kohoutek, M; Zábojníková, M; Pospísková, M; Ostrízková, L; Gharibyar, M (Journal of the European Academy of Dermatology and Venereology, 2010)
BACKGROUND: Epidermal growth factor receptor inhibitors are recently utilized by oncologists in advanced cases of certain malignancies. However, these agents are associated with numerous cutaneous adverse reactions. OBJECTIVE: To systematically review the cutaneous toxicity of cetuximab-treated patients. METHODS: An analysis of a series of 24 patients (20 men and 4 women) treated with cetuximab (12 patients with head and neck cancer and 12 patients with colorectal cancer) was performed with respect to relevant clinical characteristics. RESULTS: A total of 22 patients (91.7%) developed pustular or maculopapular follicular eruption, often referred to as acneiform rash. One patient (4.2%) developed paronychia in the course of cetuximab therapy. All patients with head and neck cancer had a combination treatment with radiotherapy and experienced radiation dermatitis accompanied by skin xerosis. Anaphylactic reaction was observed in three patients (12.5%). CONCLUSIONS: The most frequent cutaneous side effect reported in this series was acneiform eruption. The authors observed that all women with acneiform rash had only limited facial involvement, whereas all but one man experienced more widespread lesions of the face, the back and the chest. We found no association between the extent and severity of cutaneous eruptions (grade 1 vs. grade 2) and patients' response to therapy.
Keywords: senioři; nádory hlavy a krku; Prevalence; stupeň závažnosti nemoci; senioři nad 80 let; kolorektální nádory; Retrospective Studies; výsledek terapie; monoklonální protilátky; Middle Aged; Colorectal Neoplasms; mužské pohlaví; prevalence; Head and Neck Neoplasms; Acneiform Eruptions; Antibodies, Monoclonal; Adult; Antineoplastic Agents; Aged, 80 and over; ženské pohlaví; protinádorové látky; akneiformní erupce; retrospektivní studie; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; lidé středního věku; Cetuximab; dospělí; Female; Aged; Severity of Illness Index; Treatment Outcome; cetuximab; lidé; Male